A study on Bank Application - Garg, Prince (Journal of Advanced Research in Information Technology, Systems and Management, 2021)
As we are beginners and have no practical experience in the field of sales force application development and moreover the Banking Systemis very wide. So, we limit the scope of our project by computerizing the following fields of the Banking System: - • Account Opening. • Daily Transactions. • Loan Sanctions. • Account Maintenance. • Search 1. Searches record of a particular Account Holder. 2. Searches the record for a each type of Account(s). • Savings Account • Current Account • Loan Account 1. Searches the record of a particular organization’s Account Holders. 2. Account created by name. 3. Select Bank when you create your Account. 4. Have some limitation according the type of account. 5. It is more secure